THE LEVEL OF IMPLEMENTATION OF THE SEVEN EFFORTS OF BALI CATTLE IN MENGESTA VILLAGE - N. N. D. P., Utami; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the level of implementation of the seven efforts of bali cattle and the associated factors. The research was conducted in Mengesta Village, Penebel District, Tabanan Regency, Bali, from February to April 2023. The location was selected using purposive sampling, and respondents were chosen through stratified random sampling, totaling 72 individuals. Data were analyzed descriptively and using the Spearman Rank Correlation Coefficient. The results of the study indicated that the level of implementation of the seven efforts of bali cattle in Mengesta Village was categorized as moderate. Factors such as non-formal education, the participation of farmers in livestock groups, the position of farmers within existing social organizations in the village, knowledge, attitudes, skills, communication intensity, as well as perceived social, cultural, and economic impacts on farmers, showed a highly significant relationship (P<0.01) with the level of implementation of the seven efforts of bali cattle. The factor of the number of  bali cattle owned showed a significant relationship (P<0.05) with the level of implementation of the seven efforts of bali cattle. The formal education factor had a significant relationship (P<0.10) with the level of implementation of the seven efforts of bali cattle. Factors such as age, the number of family dependents, land ownership, and the duration of Bali cattle farming showed no significant relationship (P>0.10) with the level of implementation of the seven efforts of bali cattle.  Conclusion:  1) The level of implementation of the seven efforts of bali cattle in Mengesta Village falls within the moderate category;  2) Factors associated with the level of implementation of the seven efforts of bali cattle include formal education, non-formal education, the number of Bali cattle owned, participation of farmers in livestock groups, the position of farmers within existing social organizations in the village, knowledge, attitudes, skills, communication intensity, as well as perceived social, cultural, and economic impacts on farmers.